The influence of employee service on customer satisfaction at café V2 coffee space Tembalang - Azis Nur Rosyid; Sri Yulianto Fajar Pradapa; Artin Bayu Mukti (Surya Hijau Manfaat, 2023)
This research was conducted to analyze guest comments and determine customer satisfaction at V2 Coffee Space Tembalang Cafe. The method used in this research is descriptive, while the method of presenting the data is quantitative by taking the research site V2 Coffee Space Tembalang Cafe. The data collection techniques are observation, guest comment and literature study. The results of data analysis show that customers who come to Cafe V2 Coffee Space Tembalang with 50 respondents stated as follows: 1) Customer responses about guest comments on Food quality can be said to be good as seen in the results of the analysis, 7 people stated Excellent, 32 people stated Very Good, 1 person stated Fair. 2) Customer responses about Guest Comment on menu Variety can be said to be good as seen in the analysis results, 10 people stated Excellent, 30 people stated Very Good, 10 people stated Fair. 3) Customer responses about Guest Comment on Food Quality can be said to be quite good as seen in the analysis results, 14 people stated Excellent, 25 people stated Very Good, 5 people stated Fair, 6 people stated Poor. 4) Customer responses about guest comment on Food Quality can be said to be good as seen in the results of the analysis, 21 people stated Excellent, 28 people stated Very Good, 1 person stated Fair.